Rethinking Carbohydrate Synthesis: Stereoretentive Reactions of Anomeric Stannanes. Issue 13 (13th December 2018) - Zhu, Feng; O'Neill, Sloane; Rodriguez, Jacob; Walczak, Maciej A.
Abstract: In this Concept article, recent advances are highlighted in the synthesis and applications of anomeric nucleophiles, a class of carbohydrates in which the C1 carbon bears a carbon–metal bond. First, the advantages of exploiting the carboanionic reactivity of carbohydrates and the methods for the synthesis of mono‐ and oligosaccharide stannanes are discussed. Second, recent developments in the glycosyl cross‐coupling method resulting in the transfer of anomeric configuration from C1 stannanes to C ‐aryl glycosides are reviewed. These highly stereoretentive processes are ideally suited for the preparation of carbohydrate‐based therapeutics and were demonstrated in the synthesis of antidiabetic drugs. Next, the application of the glycosyl cross‐coupling method to the preparation of Se‐glycosides and to glycodiversification of small molecules and peptides are highlighted. These reactions proceed with exclusive anomeric control for a broad range of substrates and tolerate carbohydrates with free hydroxyl groups. Taken together, anomeric nucleophiles have emerged as powerful tools for the synthesis of oligosaccharides and glycoconjugates and their future applications will open new possibilities to incorporate saccharides into small molecules and biologics. Abstract : Put the metal to the carbon : This Concept article highlights recent advances in the synthesis and applications of anomeric nucleophiles, a class of carbohydrates in which the C1 carbon bears a carbon–metal bond.